Effect of short term aerobic exercise on fasting and postprandial lipoprotein subfractions in healthy sedentary men. Issue 1 (December 2015) - Sabaka, Peter; Kruzliak, Peter; Balaz, David; Komornikova, Andrea; Celovska, Denisa; Cammarota, Giovanni; Kusendova, Katarina; Bendzala, Matej; Rodrigo, Luis; Dukat, Andrej; Kwon, Taeg; Dvorakova, Magdalena; et al.
Abstract Background Our goal was to investigate the effect of short term exercise on fasting and postprandial lipoprotein profile. Methods Healthy sedentary men exercised 20 min for four days. The intensity of exercise was modulated to maintain 75–80 % of a calculated HRmax. Before and after the exercise program, fasting and postprandial (4 h after standard meal) concentrations of lipoprotein subfractions were measured by an electrophoresis in polyacrylamide gel and total concentrations of TAG, LDL and HDL by enzymatic colorimetric method. After 2 days of rest, fasting and postprandial concentrations of lipoprotein fractions and subfractions were measured to determine a persistency of a changes in the lipoprotein profile. Results 4 days of physical exercise led to statistically significant decrease of concentration of triacylglycerol in fasting (76.29 ± 20.07, 53.92 ± 10.90, p  < 0.05) and postprandial state (139.06 ± 23.72, 96.55 ± 25.21, p  < 0.05) VLDL in fasting (21.88 ± 3.87, 18.00 ± 3.93, p  < 0.05) and postprandial state (23.88 ± 3.52, 19.25 ± 3.62, p  < 0.05), total cholesterol in fasting (162.26 ± 23.38, 148.91 ± 17.72, p  < 0.05) and postprandial state (163.73 ± 23.02, 150.08 ± 18.11, p  < 0.05). Atherogenic medium LDL decreased also in fasting (9.89 ± 3.27, 6.22 ± 2.55, p  < 0.001) and postprandial state (8.88 ± 6.51, 6.88 ± 5.57, p  < 0.001). However decrease of large IDL (25.38 ± 3.54, 23.88 ± 3.91, p < 0.05) and large LDL particles (42.89 ± 11.40, 38.67 ± 9.30) was observed only in postprandial state. Total HDL concentration remained unchanged but we observed statistically significant decrease of small HDL particles in fasting (6.11 ± 2.89, 4.22, p < 0.05) and postprandial state (6.44 ± 3.21, 4.56 ± 1.33, p < 0.05). Concentration of these particles are associated with progression of atherosclerosis. All changes of fasting and postprandial lipoprotein profile disappeared after 2 days of rest. Conclusion Just 4 daily settings of 20 min of physical exercise can lead to significant positive changes of fasting and postprandial lipoprotein profile.